1988
DOI: 10.2170/jjphysiol.38.689
|View full text |Cite
|
Sign up to set email alerts
|

Acute exhaustive exercise changes the metabolic profiles in slow and fast muscles of rat.

Abstract: The effects of acute endurance running on the metabolic profiles of rat skeletal muscle were studied. Male Wistar strain rats were continuously run on a treadmill for 1 h (speed, 35 m/min; grade, 0 degrees). Soleus (SOL) and extensor digitorum longus (EDL) were removed after 30-min running, and a 0, 1, 6, 24, 48, and 72 h post-exercise, and enzymes activity (CK, LDH, PFK, PK, SDH, and MDH) and substrates contents (glycogen and pyruvate) were measured biochemically. The time course of the enzyme activities show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…These results suggest the possibility of selective plasticity and modification of muscle fibres depending on exercise characteristics and intensities as reported by Edgerton et al, (1969) and Edgerton (1970). Glycolytic and oxidative enzymes' activities in skeletal muscle following acute endurance exercise have been observed (Takekura & Yoshioka, 1988) and are clearly correlated with enlargement and/or swelling of mitochondria (Bryant et al, 1958). Considering these reports, it is proposed that muscle fibre hypertrophy was influenced by some neurotrophic actions.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…These results suggest the possibility of selective plasticity and modification of muscle fibres depending on exercise characteristics and intensities as reported by Edgerton et al, (1969) and Edgerton (1970). Glycolytic and oxidative enzymes' activities in skeletal muscle following acute endurance exercise have been observed (Takekura & Yoshioka, 1988) and are clearly correlated with enlargement and/or swelling of mitochondria (Bryant et al, 1958). Considering these reports, it is proposed that muscle fibre hypertrophy was influenced by some neurotrophic actions.…”
Section: Discussionsupporting
confidence: 51%
“…The enzyme activity in the muscle fibre tended to rise along with the exercise and to return to the resting level after 48 h of exercise (Takekura & Yoshioka, 1988). Therefore, all rats of the training groups were used for 48 h after the last exercise programme.…”
Section: Methodsmentioning
confidence: 99%
“…The enzyme activity of the skeletal muscle increased following acute exhaustive exercise and normalized after 48 h (TAKEKURA and YosHIOKA, 1988a). Furthermore, GoLLNICK and KING (1969) reported that swelling and/or enlargement of mitochondria in the muscle cells occurred following acute exhaustive exercise.…”
Section: Methodsmentioning
confidence: 98%
“…ATP provides the required energy for contraction–relaxation cycle of muscle. A major source of ATP under anaerobic conditions is creatine phosphorylated by creatine phosphokinase (CPK), a muscle‐specific enzyme ( Takekura & Yoshioka 1988). Myokinase is another muscle‐specific enzyme which catalyses the formation of one ATP molecule from two ADP molecules.…”
mentioning
confidence: 99%